Hubungan antara Lingkungan Rumah dan Sanitasi akanan dengan Keberadaan Tikus di Kabupaten Boyolali - RIKA, RITTA RUM (2016)
Rats are animals that have a habit of gnawing rodents. Location rat's nest is usually hidden, moist, not waterlogged. Houses that are not meeting the rat (rodent proof) and is not maintained then at certain points would be a rat's nest. Rats nest outdoors usually in the form of a hole in the ground, in the trash, and dirty place. This study aims to examine the relationship between the home environment and sanitation with the presence of rats in Boyolali. The study used a case-control study design with a ratio of 1: 1. The entire population of people living in Boyolali district in 2014-2015. Samples are cases of patients with leptospirosis in Boyolali totaled 32 while the control sample is a nearest neighbor (side / rear of the house patients). Collecting data using observation sheet, data analysis using chi square and fisher exact. Results of the analysis concludes that there is a link on variable kinds of flooring (p =0,001; OR=11,182; 95% CI = 2,580 to 48,456) and the type of wall (p=0,002; OR=8,400; 95% CI=2,104 to 33,531). No relation to the variable habit of turning off lights (p=0,507), the condition of bins (0,742), the construction of the roof (p=0,507), the presence of lines of mice to the roof (p=0,156), the condition SPAL (p=0,115), the habit of saving means of food (p=1,000), the habit of storing food and beverages (p=0,574). Suggested to health workers in order to improve sanitation and healthy homes in Boyolali district.